2021
DOI: 10.1021/acsabm.0c01084
|View full text |Cite
|
Sign up to set email alerts
|

A Polycaprolactone (PCL)-Supported Electrocompacted Aligned Collagen Type-I Patch for Annulus Fibrosus Repair and Regeneration

Abstract: Deformity or fissure within the annulus fibrosus (AF) lamellar structure often results in disc herniation leading to the extrusion of nucleus pulposus (NP), which pushes the adjacent nerve, causing low back pain. Low back pain, frequently associated with the degeneration of the intervertebral disc (IVD), affects around 80% of the population worldwide. The difficulty in mimicking the unique structural characteristics of the native AF tissue presents several challenges to the tissue engineering field for the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Their acellular scaffolds demonstrated tensile modulus values similar to native AF and supported AF cell viability and an increase in metabolic activity over 7 days 47 . Dewle et al created PCL reinforced collagen fiber scaffolds that demonstrated uniaxial tensile properties similar to that of native AF and supported caprine AF cell viability, proliferation, adhesion, alignment along the fibers, and an increase in collagen type I mRNA expression 68 . While several other multilaminate scaffolds have been developed and characterized, 31 the AFRP described herein represents a simple approaches to creating a biomimetic, collagen‐based, multilaminate angle‐ply scaffold that has both mechanical and biological properties conducive to supporting annular repair.…”
Section: Discussionmentioning
confidence: 99%
“…Their acellular scaffolds demonstrated tensile modulus values similar to native AF and supported AF cell viability and an increase in metabolic activity over 7 days 47 . Dewle et al created PCL reinforced collagen fiber scaffolds that demonstrated uniaxial tensile properties similar to that of native AF and supported caprine AF cell viability, proliferation, adhesion, alignment along the fibers, and an increase in collagen type I mRNA expression 68 . While several other multilaminate scaffolds have been developed and characterized, 31 the AFRP described herein represents a simple approaches to creating a biomimetic, collagen‐based, multilaminate angle‐ply scaffold that has both mechanical and biological properties conducive to supporting annular repair.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to mechanically repair AF were developed (sutures, patches) but none of these techniques significantly altered annular healing in animal models nor demonstrated long-term benefits in clinical trials [ 175 ]. It is crucial that AF implants maintain adhesion to target tissue, especially under strain.…”
Section: Spheroid-based Cell Therapies For Degenerative Disc Diseasementioning
confidence: 99%
“…It is crucial that AF implants maintain adhesion to target tissue, especially under strain. Novel AF sealants have been generated and showed promising results [ 175 , 176 , 177 , 178 ]. Compared to acellular therapies, cell-based implants improve ECM deposition and organization in animal studies and show more successful AF remodeling in the long-term [ 178 ].…”
Section: Spheroid-based Cell Therapies For Degenerative Disc Diseasementioning
confidence: 99%
“…PCL is a frequently used polymer in biomaterials, tissue engineering, and controlled delivery applications owing to its biocompatibility and biodegradability 39 . PCL is a semi‐crystalline polymer with a low degradation rate and good mechanical properties allowing it to have a high degree of flexibility and tensile strength, making it suitable for use in healthcare applications 40,41 . PCL is a hydrophobic polymer, which is advantageous for the preparation of hydrophobic active ingredients in common organic solvent systems.…”
Section: Introductionmentioning
confidence: 99%
“… 39 PCL is a semi‐crystalline polymer with a low degradation rate and good mechanical properties allowing it to have a high degree of flexibility and tensile strength, making it suitable for use in healthcare applications. 40 , 41 PCL is a hydrophobic polymer, which is advantageous for the preparation of hydrophobic active ingredients in common organic solvent systems. Additionally, it has great compatibility with volatile solvents simplifying the production process.…”
Section: Introductionmentioning
confidence: 99%